Machine Learning Algorithms applied in a Service Platform for Professional Services Case Study - Manrique Acha, Renato Alejandro (2023)
This paper presents alternatives for the implementation of a Market Place called “Clic”, considering the technological infrastructure necessary for its operation based on Machine Learning algorithms. During the elaboration of this paper, surveys were conducted to both users qualified as "Clients" and "Professionals" about the intentionality of use and the probability of payment for the publication of their services in the platform. This paper presents the recommended steps for the composition of the Clic company, the way the information is collected for Machine Learning and the data obtained from the users, the recommended environments for the development of the application, the results of the surveys carried out, the feasibility of the Machine Learning algorithm, numerical data of financial feasibility for the execution of the project.